Effectiveness of Hearing AIDS For Vocabulary Development Among Preschool Children - Anila Inam; Nabeel, Tanzila (JIE, 2025)
To find out the effectiveness of hearing aids for vocabulary development among preschool children, a descriptive comparative -research study was conducted. It was hypothesized that a significant difference was observed in the achievement of vocabulary in those hearing-impaired children who used hearing aids than those who had not been intervened by hearing aids. The expressive vocabulary was measured by an indigenous dichotomous scale consisting of 95 items. The responses were scored as 1 for verbal and 0.5 were given to non-verbal and 0 for nonrespondents. A pre-testing of the tool was done before the final administration of the tool. A purposive sampling technique was employed in selecting the sample. The sample was selected by an initial assessment form to select subjects for same after the administration of the tool to a sample of 30 preschool hearing- impaired children, the scores were analyzed on SPSS to find out the results. The result showed a higher level of oral expressive vocabulary among children who were the users of hearing aids as compared to those children who were not intervened by hearing aids. auditory, and speech training, and proper management and maintenance of the hearing aids had a significant role in vocabulary development among preschool children.